ChemInform Abstract: Antibacterial Activity of Novel Cu2ZnSnS4 Nanoparticles Against Pathogenic Strains. Issue 11 (February 2016) - Kumar, R. Saravana; Maddirevula, Sateesh; Easwaran, Maheswaran; Dananjaya, S. H. S.; Kim, Moon‐Deock
Abstract: Hollow tubular Cu2 ZnSnS4 (CZTS) particles are prepared by heating an ethylene glycol solution of CuCl2, ZnCl2, SnCl4, and thiourea in a molar ratio of 2:1:1:4.5 (215 °C, 6 h).